A critical insight into the effectiveness of research methods evolved to secure IoT ecosystem - Khan, Burhan ul Islam; Olanrewaju, Rashidah Funke; Anwar, Farhat; Mir, Roohie Naaz; Najeeb, Athaur Rahman (Inderscience Publishers, 2018)
Increasing proliferation of IoT has led to an evolution of various devices for realizing the smart features of ubiquitous applications. However, the inclusion of such a massive pool of devices with different computational capabilities, network protocols, hardware configurations, etc. also causes a higher number of security threats. Security professionals, organizations, and researchers are consistently investigating the security problems associated with IoT ecosystem and are coming up with different forms of solution sets. This paper presents a snapshot of the existing research work being carried out towards the security of IoT and assesses their strengths and weaknesses. The paper also explores the current research trend and presents the latest security methods being implemented and outlines the open research issues associated with it. The paper contributes to offering an accurate picture of the effectiveness of the existing security system in IoT.